Potentialites Nutritionnelles et Dietetiques des Chenilles Et Insectes Consommes en Rd Congo. Cas de Fruit de Mer, Cirina Forda, Imbrasia Ertli, Ruspolia Differens et Augosoma Centaurus - Par , Musala Kiyula François; Mwidya , Seya Crispin; Kanga-Kanga , Mfuni Rene; Mwana , Mwamba M. Josee; Ntumba , Tshiovu Donatien; Minga, Shanga Patrick; Kavugho , Sivayiketera Esperance; Nyamurombo , Vumilia Louange (Journal of Food Sciences, 2025)
Objective: This research entitled "Nutritional and dietary potential of caterpillars and insects consumed in the DRC; case of seafood, Cirina forda, Imbrasia Ertli, Ruspolia dif]ferens and Augosoma centaurus" aims to promote and popularize the consumption of this category of food, because they compete with meat and fish in terms of protein and lipid content and also fruits and vegetables in terms of richness in vitamins and minerals. Finally, the aim is to make available the scientific data necessary for nutrition and dietetics. Methodology: We will conduct a bibliographic search to establish a state of the issue, define the objective, identify the originality and plan this study. Then, we will purchase and collect samples of caterpillars consumed in the DRC; we will carry out chemical analyses including humidity, total ash, crude proteins, lipids, total carbohydrates and mineral elements which were measured using the ICP 8300. Observation: we were able to say that the edible caterpillars analyzed are energetic ranging from 303 (Ruspolia Differens) to 493Kcal/g for Imbrasia Ertli, and represent an important source of proteins (ranging from 50.79 Ruspolia differens to 70.3 Augosoma centaurus). By their richness in Mg [ranging from 288.8 (Imbrasia Ertli) to 1476 mg/Kg (Augosoma Centaurus)]; In Ca [ranging from 202.7 (Imbrasia Ertli) to 950.8 mg/Kg for Fruit de Mer]; The caterpillars respectively have a preventive action against cancer and play a very active role in bone formation. Caterpillars have a curative power against arrhythmia and heart failure due to their richness in Ca, Mg, K and low fat content including in ascending order Ruspolia differens, Augosoma centaurus. They are remineralizing due to their richness in Mg of which the best is Augosoma centaurus; in Ca of which the best is seafood. They are anti-anemic due to their richness in Fe of which the best is Cirina Forda; in proteins of which the best is Imbrasia Ertli and in vitamins of group B (Vit. B12). Recommendation: the rational food consumption of caterpillars and insects in the same way as other foods is recommended and particularly in case of protein-energy malnutrition.